PENETAPAN BIAYA PRODUKSI TAYANGAN IKLAN DI MADU TV BIRO BLITAR - Agustyas Retno Hernani; Endah Masrunik (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2020)
Production costs are costs contained in a product or service, so the costs incurred must be able to be identified and calculated correctly, so that the total production costs incurred are truly accurate. The purpose of this study is to find out what costs are contained in the determination of production costs for an advertisement and how to calculate them. The method used is descriptive qualitative, where data is collected by interview and observation method and then draws a conclusion from the results of these interviews and observations. The results of this study indicate that the production costs incurred for an advertisement are determined by the bureau which consists of equipment rental costs and crew costs or salaries (excluding basic salaries) then the amount is calculated and added with transportation costs